First data from the new amphibian road-kill hotspot at Vinogradniška pot in Razvanje (NE Slovenia) - Lobnik, Rok (Natura Sloveniae, 2025)
There are more than 1500 road segments, where large amphibian mortali-ties are recorded in Slovenia. One of such road-kill hotspots is Vinogradniška pot at Razvanje (NE Slovenia), where censuses of migrating amphibians were carried out in spring of 2019, 2020, 2021 and 2024 alongside actions to prevent road death that have been taking place since 2018, albeit irregularly. Here, the first data from those censuses are presented. Four amphibian species were recorded migrating over the road, specifically common toad (Bufo bufo), common frog (Rana temporaria), agile frog (R. dalmatina) and Italian crested newt (Triturus carnifex). The most numerous was B. bufo, of which 500–1000 individuals mi-grated over the road annually and represented about 99% of individuals of all recorded amphibian species. Male B. bufo outnumbered females by 4–12:1 and species mortality was fairly low (between 5 and 12%), but was deliberately artificially reduced. Amphibian activity was lower later in the evening and had a significant moderate positive correlation with the air temperature. The data presented indicate the importance of amphibian spring migration monitoring also over low-traffic roads, which are rarely the focus of similar studies.
Keywords: dvoživke; Razvanje; Vinogradniška pot; zoologija